Serum vitamin D status and circulating irisin levels in older adults with sarcopenia - Wang, Yawen; Gu, Yeqing; Huang, Jian; Wu, Hongmei; Meng, Ge; Zhang, Qing; Liu, Li; Zhang, Shunming; Wang, Xuena; Zhang, Juanjuan; Sun, Shaomei; Wang, Xing; et al. (Frontiers in Nutrition, 2022)
Background: Emerging evidence suggests sarcopenia, which is involved in the serum vitamin D deficiency and development of abnormal muscle metabolism, is predominately centered in the general older population. In the present study, we aimed to explore the relationship between the level of serum vitamin D and irisin concentrations in the older adults with sarcopenia. Methods: A cross-sectional study was conducted which included 422 sarcopenia participants (146 males and 276 females). Sarcopenia was assessed according to the recommended diagnostic criteria of the Asia Working Group for Sarcopenia (AWGS). The levels of serum 25-hydroxyvitamin D (25(OH)D), 25-hydroxyvitamin D2 (25(OH)D2) and 25-hydroxyvitamin D3 (25(OH)D3) were determined by LC-MS/MS. Irisin levels were measured by enzyme-linked immunosorbent assay (ELISA). The relationship between serum concentration of vitamin D and irisin were determined using multiple linear regression analysis. Results: After adjustment for potential confounding factors, a significant and positive relationship between changes in irisin across 25(OH)D, and 25(OH)D3 was observed (standard regression coefficients of 0.150 and 0.151, respectively, P <0.05). However, no significant relationship was observed between serum vitamin D concentrations and irisin levels in males. Conclusions: This study demonstrated that a higher level of serum vitamin D is independently related to the increment of irisin in sarcopenia females, not in males. These investigations need to be verified in other large-scale prospective studies.